2016
DOI: 10.1515/joc-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward Equalizers for MDM–WDM in Multimode Fiber Interconnects

Abstract: In this paper, we present new tap configurations of a feedforward equalizer to mitigate mode coupling in a 60-Gbps 18-channel mode-wavelength division multiplexing system in a 2.5-km-long multimode fiber. The performance of the equalization is measured through analyses on eye diagrams, power coupling coefficients and bit-error rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Although the LMS algorithm has a low computational complexity, its training sequence adds an overhead and thus reduces the performance of the system. Moreover, the CMA requires a suitable learning step; the equalizer converges slowly with small steps and cannot converge with large steps for accurate estimation [8].In [13], Koebele et al, discuss the use of CMA to update the equalizer coefficients, although, CMA provides low computational complexity, it has a poor performance. This is due to the instability and a slower convergence rate compared with LMS algorithm [14,15].…”
Section: Equalization Schemes In Mdm Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the LMS algorithm has a low computational complexity, its training sequence adds an overhead and thus reduces the performance of the system. Moreover, the CMA requires a suitable learning step; the equalizer converges slowly with small steps and cannot converge with large steps for accurate estimation [8].In [13], Koebele et al, discuss the use of CMA to update the equalizer coefficients, although, CMA provides low computational complexity, it has a poor performance. This is due to the instability and a slower convergence rate compared with LMS algorithm [14,15].…”
Section: Equalization Schemes In Mdm Systemmentioning
confidence: 99%
“…To mitigate the effects of mode coupling in the MDM system, several techniques have been proposed [7,8]. However, the hardware-based equalizer cannot provide an acceptable performance with time-varying channels, due to the implementation complexity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors experimentally reported feasible transmission of 2 LP modes × 4 phase-shift-keyed optical codes × 10-Gbps on-off-keyed data streams over a 42 km fiber length using a single-mode and a multi-mode fiber without the application of dispersion compensation. T. Masunda et al proposed hybrid MDM and WDM architecture to realize high-speed MMF interconnects [24]. Six independent vertical-cavity surface-emitting laser diodes are used, where each wavelength generates three distinct Laguerre-Gaussian (LG) modes to realize 18 parallel channel transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, multimode fibers using in MDM communication systems only support a relatively small number of guided modes which are thus called few-mode fibers because a large number of guided modes cause degraded signals from highorder and inter-modal dispersion issues associated with nonlinear effects [4,5]. However, and silicon crystals in the silicon waveguide, hybrid WDM-MDM systems are still able to apply for short-haul optical communication systems [6][7][8][9] and optical interconnects [10][11][12] thanks to the support of advanced dispersion compensation techniques [13,14]. Basically, technology developers typically use graded-index fibers optimized for minimum differential modal group delay (DMGD) because such fibers allow the use of simpler receiver technology.…”
Section: Introductionmentioning
confidence: 99%